Differences in Abnormal Return, Trading Volume Activity, Firm Value Volatility Before and After Stock Split: Perbedaan Abnormal Return, Trading Volume Activity, Nilai Perusahaan Volatilitas Sebelum dan Sesudah Stock Split - Mujaiyinul Alam; Sriyono Sriyono (Academia Open, 2021)
This study aims to determine and understand the differences in Abnormal Return, Trading Volume Activity, Firm Value, Volatility before and after the stock split. This research is a type of quantitative research with hypothesis testing. In this study, from a population of 145 Indonesian manufacturing companies listed on the Indonesia Stock Exchange for the 2010-2019 period, 40 companies conducted stock splits. In order to solve the problems contained in the formulation of the problem in this study, the method used is the Paired T Test or Wilcoxon Signed Rank analysis model depending on the distribution of the data, the analysis is carried out using the help of the Stata software program. The results of this study prove that abnormal returns before and after the stock split have a significant difference with the test results of 0.0344 difference. Trading volume activity before and after the stock split there is a significant difference in the test results of 0.0175. The value of the company before and after the stock split there is a significant difference in the test results of 0.0178. Volatility before and after the stock split there is a significant difference in the test results of 0.0196.